2019
DOI: 10.1117/1.jmi.6.1.014502
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo Barrett’s esophagus digital pathology stage classification through feature enhancement of confocal laser endomicroscopy

Abstract: Barrett's esophagus (BE) is a premalignant condition that has an increased risk to turn into esophageal adenocarcinoma. Classification and staging of the different changes (BE in particular) in the esophageal mucosa are challenging since they have a very similar appearance. Confocal laser endomicroscopy (CLE) is one of the newest endoscopy tools that is commonly used to identify the pathology type of the suspected area of the esophageal mucosa. However, it requires a well-trained physician to classify the imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In this study, their model achieved a mean classification accuracy of 0.98 in distinguishing between benign and potentially malignant tongue lesions 37 . Studies on WSIs of OPMDs are lacking but importantly, parallels may be drawn with AI‐based approaches on clinicopathologic parameters of premalignant disorders in different sites such as the esophagus (Barrett's esophagus) and the cervix (cervical intraepithelial neoplasia) 38,39 . Thus, future studies focused on OPMDs would greatly benefit the field especially in tackling the large intra‐ and inter‐observer variability that occurs in oral dysplasia grading.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In this study, their model achieved a mean classification accuracy of 0.98 in distinguishing between benign and potentially malignant tongue lesions 37 . Studies on WSIs of OPMDs are lacking but importantly, parallels may be drawn with AI‐based approaches on clinicopathologic parameters of premalignant disorders in different sites such as the esophagus (Barrett's esophagus) and the cervix (cervical intraepithelial neoplasia) 38,39 . Thus, future studies focused on OPMDs would greatly benefit the field especially in tackling the large intra‐ and inter‐observer variability that occurs in oral dysplasia grading.…”
Section: Discussionmentioning
confidence: 90%
“…While deep learning has made significant advances and progressed the field of oncologic pathology, its use with respect to oral oncology is still in the nascent stage (Table 1) however, the extent of data analyzed was limited to demographic, clinicopathologic, or genomic data. 26,[30][31][32] Chang et al 33 38,39 Thus, future studies focused on OPMDs would greatly benefit the field especially in tackling the large intra-and inter-observer variability that occurs in oral dysplasia grading.…”
Section: Ai In Oral Oncologymentioning
confidence: 99%
“…Veronese et al[ 20 ] used CLE images, and the results showed that the system could accurately distinguish gastric metaplasia (GM), intestinal metaplasia (IM), and neoplasia. Ghatwary et al[ 23 ] showed that the sensitivity of the system using CLE images to diagnose IM and neoplasia was significantly higher than that to diagnose GM. Similarly, the CAD system established by Hong failed to identify GM, the sensitivity of diagnosing IM was not significantly different from that of the above study, and the sensitivity of diagnosing neoplasia was slightly decreased[ 24 ].…”
Section: Ai In Endoscopic Detection Of Early Ecmentioning
confidence: 99%
“…Confocal laser endomicroscopy (CLEM) has also been applied for endoscopic diagnosis of gastrointestinal neoplastic lesions including Barrett’s dysplastic lesions [ 113 ]. Recently, a stratified diagnostic strategy for diagnosis of precancerous and cancerous lesions by CLEM was confirmed to have a high level of accuracy [ 114 ], while the additional effect of probe-based CLEM was also proven for detection of dysplastic lesions in BE as compared to magnifying NBI endoscopy alone [ 115 ]. Thus, molecular CLEM is considered to be a novel method for diagnosis of dysplastic Barrett’s lesions that allows for visualization of cellular processes in real-time by combinations of a variety of either molecular probes or peptides with fluorescent items.…”
Section: Endoscopic Findings Showing Possible Predictive Biomarkermentioning
confidence: 99%